2014
DOI: 10.1021/ol4036177
|View full text |Cite
|
Sign up to set email alerts
|

Concise synthesis of Didebromohamacanthin A and Demethylaplysinopsine: Addition of Ethylenediamine and Guanidine Derivatives to the Pyrrole-Amino Acid Diketopiperazines in Oxidative Conditions

Abstract: Oxidative nucleophilic addition of ethylenediamine and guanidine derivatives to pyrrole-amino acid diketopiperazines was shown to provide substituted 5,6-dihydro-2(1H)-piperazinones, quinoxalinones, and 2-aminoimidazolones. On the basis of this methodology, a concise approach to natural products didebromohamacanthin A and demethylaplysinopsine has been demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Therefore, the three monomeric aplysinopsins 1 – 3 were prepared in a single step from 3‐formylindole derivatives ( 8 or 9 ) and the suitable creatinine ( 10 or 11 )14 to set the stage for the dimerization studies (Scheme ). At first, the above‐mentioned Diels–Alder cycloaddition was investigated with monomer 1 under different conditions, including heating for several days in DMF, use of SbCl 3 15 and the Ledwith–Weitz aminium salt (SbCl 6 N( p ‐BrPh) 3 ),16 or ultra‐high pressures, but the desired transformation was not observed 17.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the three monomeric aplysinopsins 1 – 3 were prepared in a single step from 3‐formylindole derivatives ( 8 or 9 ) and the suitable creatinine ( 10 or 11 )14 to set the stage for the dimerization studies (Scheme ). At first, the above‐mentioned Diels–Alder cycloaddition was investigated with monomer 1 under different conditions, including heating for several days in DMF, use of SbCl 3 15 and the Ledwith–Weitz aminium salt (SbCl 6 N( p ‐BrPh) 3 ),16 or ultra‐high pressures, but the desired transformation was not observed 17.…”
Section: Methodsmentioning
confidence: 99%
“…The known compounds (AE)-4 -15, 17 -20, and 22 were identified as (S)-5-methoxy-D 3 -pyrrolin-2-one ((+)-4), [24] (R)-5-methoxy-D 3 -pyrrolin-2-one ((À)-4) [24] (the (5R)-and (5S)-configurations were determined by comparing the optical rotations with those of (AE)-2), (Z)-N-(3-(2,5-dioxoimidazolidin-4-ylidene)propyl)-1H-pyrrole-2-carboxamide (5), [25] b-alanine methyl esters (6), [26] N-(pyrrole-2-carbonyl)glycine methyl esters (7), [27] N-(2-hydroxyethyl)-1H-pyrrole-2-carboxamide (8), [28] N-formylpyrrole-2-carboxamide (9), [29] 1H-pyrrole-2-carboxamide (10), [29] 4-bromo-1H-pyrrole-2-carboxamide (11), [30] 5-bromo-1H-pyrrole-2-carboxamide (12), [30] 1H-pyrrole-2-carboxylic acid (13) [31] , 4-bromopyrrole-2-carboxylic acid (14), [32] 5-bromopyrrole-2-carboxylic acid (15), [32] agelasine B (17), [8] agelasine J (18), [15] nemoechine G (19), [10] 2-oxoagelasine B (20), [33] and (À)-agelasidine C (22), [34] by comparing their spectra data with those reported earlier.…”
Section: Structure Elucidationmentioning
confidence: 99%
“…The electron density observed for 27 is consistent with either an OH or NH2 substituent at C-5, We re-examined a sample of 27 by LCMS and HRMS and this showed that the sample was a mixture of 27 (~95%) and the hydrated compound 27 (~5%)(Figure 8). Co-formation of C-5 benzylidine thiohydantoins with hydrated C-5 hydroxy/C-5 benzyl thiohydantoins has been reported 47. As 27 makes additional interactions over 27, it is plausible to imagine 27 easily outcompeting 27 for the CA II binding site.…”
mentioning
confidence: 99%